DEVELOPMENT OF METHODS FOR STUDIES ON BRUCELLOSIS IN THE MILK OF GOATS AND CAMELS - Ivanov N. P.; Sarimbekova S. N.; Sultanov A. A.; Namet Aidar Myrzakhmetuly; Arysbekova A. T. (Scientific Journal of Pedagogy and Economics, 2019)
Research of milk of goats and camels on brucellosis is carried out with the help of a diagnostic kit, which consists of the following components: 1. Color antigen 1 vial (ampoule) with a volume of 2.0 cm3 . 2. Positive brucella serum of animals, 1 vial (ampoule) in a volume of 2.0 cm3 . 3. Negative serum of animals, 1 vial (ampoule) in a volume of 2.0 cm3 . 4. Freeze-dried or milk healthy by cow brucellosis, 1 bottle of 20.0 cm3 . 5. distilled water in sterile form 1 vial (ampoule) in the amount of 20.0 cm3 (for dilution of dried milk lyophilic). On vials, ampoules of each biocomponent paste the label and pack 1 piece in cardboard boxes with the presence of nests or partitions, ensuring the immobility and integrity of the vial (ampoules).The diagnostic kit is stored indoors in a dark dry place at a temperature of 2 to 14 °C. The shelf life of the set is 12 months from the date of manufacture. In the presence of foreign matter, violation of tightness of bottles (ampoules), the absence of the label of the bottle (ampoule) is rejected and must be destroyed.